1979
DOI: 10.1113/jphysiol.1979.sp012975
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of saxitoxin binding to the sodium channel of sarcolemma isolated from rat skeletal muscle.

Abstract: SUMMARY1. The characteristics of saxitoxin (STX) binding to the mammalian Na channel have been studied in purified sarcolemma isolated from rat skeletal muscle.2. STX binds specifically to isolated sarcolemma with a Kd of 1*43 x 10-9 M and Bmax of 7-8 p-mole STX bound/mg membrane protein at 0C in the presence of 140 mM-NaCl. 3. Denervation (10-14 days) results in a 43 % reduction in the density of highaffinity STX binding sites in purified sarcolemma, but the 1Kd for this class of sites is not changed.4. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
41
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 28 publications
10
41
1
Order By: Relevance
“…Measurements of the amount of Na+ were carried out in a choline chloride medium as previously Fig. 4A, B (19), synaptosomes (24), and rat muscle (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of the amount of Na+ were carried out in a choline chloride medium as previously Fig. 4A, B (19), synaptosomes (24), and rat muscle (25).…”
mentioning
confidence: 99%
“…Their number expressed per milligram of protein (Table III) The affinity of saxitoxin for its receptor was the same in innervated and denervated muscle (25,46). In contrast with the observations made after experimental denervation of rat muscle, Gruener et al (7,33) reported that TTX-resistant action potentials are not observed in pathologically nerve-impaired human muscle.…”
mentioning
confidence: 99%
“…for further purification by using an immobilized lectin specific for this carbohydrate. The lower limit of molecular weight for the sodium channel has been estimated to be 230,000-250,000, although an upper limit cannot yet be set (16). If this lower limit is assumed and one molecule of toxin is bound per 250,000-dalton unit, a theoretical maximal specific activity of 4000 pmol/mg of protein is expected.…”
mentioning
confidence: 99%
“…One of these (trimethyloxonium ion) revealed that acidic amino acids were important in the binding of TTX and STX. Pretreatment with this reagent abolished the channel's ability to bind the toxin, whereas pre-exposure of the channel to the toxin protected it from protein modification (Barchi and Weigele 1979;Doyle et al 1993;Spalding 1980;Worley et al 1986). Later, after Na channel genes were sequenced and successfully expressed in recombinant systems, mutagenesis studies pinpointed a series of carboxylate sidechain-containing amino acids in homologous positions within each of the four domains of the channel involved in binding the toxin (Terlau et al 1991) and were hypothesized to form two predominantly negatively charged rings near the ion pore.…”
Section: Effects Of Na Channel Modificationmentioning
confidence: 99%
“…Increasing temperature decreases affinity of both STX and TTX for the toxin sensitive isoforms of the Na channel (Barchi and Weigele 1979;Bay and Strichartz 1980;Weigele and Barchi 1978). Warming 20°C can reduce affinity of the toxins 10-to 20-fold.…”
Section: Temperaturementioning
confidence: 99%